Resposta das exportações e importações a choques cambiais em regime de câmbio flexível, 1999-2019 - Carvalho, Ivyan Larissa Barros de (2021)
This dissertation aims to analyze how aggregate exports and imports respond to changes in the real exchange rate, during the flexible exchange regime in Brazil. In the short term, based on a VAR with Bayesian estimator, it appears that the response of imports and exports after a change in macroeconomic conditions in 2014 has been smoothed. Imports and exports do not respond statistically significantly to changes in the real exchange rate.